Strengthening the Role of Sharia Banking in Financing Solar Power Plants to Support Sustainable Development in Indonesia - Djauhari, Haikal; Al Arif, Muhammad Nur Rianto; Hosen, Muhamad Nadratuzzaman (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2024)
The reluctance of Islamic banking to participate in financing solar power plants is primarily due to higher risk and lower economic value than fossil-based energy. This study proposes a risk management guidance and financing model to strengthen the role of Sharia Banking in financing solar power plants and support sustainable development in Indonesia. There is a significant gap in the study of risk management and the Syariah financing model for solar power plants. We used a qualitative method that involved expert consultations and literature studies to identify the risks of solar power plants. We also derived an equity-based Diminishing Musyarakah for the Sharia financing model. The study’s result is a risk management framework and a Sharia financing scheme for solar power plants. By using this framework Sharia banks can increase their participation in supporting sustainable development. Keengganan perbankan syariah untuk berpartisipasi dalam pembiayaan pembangkit listrik tenaga surya terutama disebabkan oleh risiko yang lebih tinggi dan nilai ekonomi yang lebih rendah daripada energi berbasis fosil. Studi ini mengusulkan sebuah panduan manajemen risiko dan model pembiayaan untuk memperkuat peran Perbankan Syariah dalam pembiayaan pembangkit listrik tenaga surya dan mendukung pembangunan berkelanjutan di Indonesia. Terdapat kesenjangan yang signifikan dalam studi manajemen risiko dan model pembiayaan Syariah untuk pembangkit listrik tenaga surya. Kami menggunakan metode kualitatif yang melibatkan konsultasi dengan para ahli dan studi literatur untuk mengidentifikasi risiko pembangkit listrik tenaga surya. Kami juga menurunkan Musyarakah yang semakin berkurang berbasis ekuitas untuk model pembiayaan Syariah. Hasil dari penelitian ini adalah sebuah kerangka kerja manajemen risiko dan skema pembiayaan Syariah untuk pembangkit listrik tenaga surya. Dengan menggunakan kerangka kerja ini, bank-bank Syariah dapat meningkatkan partisipasi mereka dalam mendukung pembangunan berkelanjutan.